Sistem Pendukung Keputusan Untuk Menentukan Kelayakan Penerima Bantuan Rehabilitas Rumah Tidak Layak Huni Menggunakan Metode Simpel Additive Weigting (SAW) Pada Dinas Perumahan, Permukiman Dan Pemakaman Kabupaten Tangerang - Wahyu Hadikristanto; Njai Njai; Andri Firmansyah (Teknik Informatika, Universitas Pelita Bangsa, 2021)
The Tangerang Regency Housing, Settlement and Cemetery Service has house renovation assistance for Low-Income Communities (MBR). Data input still uses manual data in the form of data such as resident documents in determining the assistance in the form of house renovation. In determining the recipient of assistance still uses subjective assessment. Analysis of Manual Calculations with the Simple Additive Weighting (SAW) method after that analysis and design were made using object-oriented methods by making use cases, activities, sequences, class diagrams and user interfaces. The results of the design can be developed to help government agencies in Tangerang Regency. Keywords: Home Rehabilitation, Simple Additive Weighting, User Interface